1997
DOI: 10.1099/00221287-143-2-405
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Candida albicans genes conferring resistance to azole antifungal agents: characterization of CDR2, a new multidrug ABC transporter gene

Abstract: Resistance to azole antifungal agents in Candida albicans can be mediated by multidrug efflux transporters. In a previous study, w e identified a t least two such transporters, C d r l p and Benp, which belong to the class of ATP-binding -cassette (ABC) transporters and of major facilitators, respectively. To isolate additional factors potentially responsible for resistance to azole antifungal agents in C. albicans, the hypersusceptibility of a Saccharomyces cerevisiae multidrug transporter mutant, Apdr5, to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
522
3
5

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 547 publications
(548 citation statements)
references
References 33 publications
18
522
3
5
Order By: Relevance
“…Two major mechanisms of azole resistance have been identified: One common resistance mechanism is the reduced intracellular accumulation of drugs, which is correlated with the increased expression of the CDR genes, members of the ABC efflux pump family, and/or of the MDR1 gene, a member of the MFS efflux pump family. 13,31,32) Other common mechanisms are increased expression of the ERG11 gene that encodes the target enzyme of azole drugs, sterol 14a-demethylase, and alteration of the enzyme due to point mutations in the gene. [32][33][34][35][36][37][38] C. albicans FCR1 gene has been reported characterization by encoding a putative 517-amino-acid protein with an N-terminal Zn 2 C 6 -type zinc finger motif homologous to that found in fungal zinc cluster regulatory factors including S. cerevisiae Pdr1p and Pdr3p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two major mechanisms of azole resistance have been identified: One common resistance mechanism is the reduced intracellular accumulation of drugs, which is correlated with the increased expression of the CDR genes, members of the ABC efflux pump family, and/or of the MDR1 gene, a member of the MFS efflux pump family. 13,31,32) Other common mechanisms are increased expression of the ERG11 gene that encodes the target enzyme of azole drugs, sterol 14a-demethylase, and alteration of the enzyme due to point mutations in the gene. [32][33][34][35][36][37][38] C. albicans FCR1 gene has been reported characterization by encoding a putative 517-amino-acid protein with an N-terminal Zn 2 C 6 -type zinc finger motif homologous to that found in fungal zinc cluster regulatory factors including S. cerevisiae Pdr1p and Pdr3p.…”
Section: Discussionmentioning
confidence: 99%
“…Cdr1p could mediate azole resistance by causing active energy-dependent extrusion of the drug out of cells. 31,39) In the present study, we used a fluorescent dye, rhoamine 6 G (R6G), which is a substrate of CDR1, to identify CDR activity because a previous study showed that the efflux of rhoamine 6 G is positively correlated with the expression of CDR1. 40) Our results for rhodamine 6 G active efflux also showed that with the susceptibilities of the strains to FLC decreased, and the extrusion of rhodamine 6 G by C. albicans increased in the presence of glucose providing energy for rhodamine 6 efflux (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Four kinds of CDR genes in C albicans have been cloned [13,[40][41][42] , but only over-expression of CDR1 and CDR2 resulted in azole resistance [43] . Tac1p is the major transcription factor needed for the regulation of CDR1 and CDR2, and is characterized by a highly conserved Zn(II) 2 Cys 6 zinc finger motif formed by six cysteines that coordinate two zinc atoms within the DNAbinding domain [11,44,45] .…”
Section: Discussionmentioning
confidence: 99%
“…These transcription factors, as well as the transcription processes, represent potential targets against MDR. Among the MDR genes regulated by zinc cluster transcription factors, the expression of CDR1 and CDR2 has received considerable attention, because their encoding ABC transporter proteins, Cdr1p and Cdr2p, could pump azoles out of cells to reduce azole accumulation as a self-defense mechanism [12][13][14][15] . Our previous studies have also demonstrated that elevated CDR1 and CDR2 levels are associated with the progression of MDR in antifungal treatment [16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…The genome sequence from S. cerevisiae has revealed the presence of as many as 28 ORFs homologous to either the ABC or the MFS family (Goffeau et al, 1997). Yeast multidrug transporters include the ABCs protein CDR1-3 from Candida albicans (Sanglard et al, 1997;Balan et al, 1997) and the MSF BEN r (CaMDR1) that renders cells resistant to cyh, benomyl, methotrexate, 4-nitro-quinoline-N-oxide, or terbinafine (Ben-Yaacov et al, 1994;Goldway et al, 1995;Sanglard et al, 1997;Gupta et al, 1998). The C. maltosa CYR R and the C. dubliniensis CdMDR1, homologous to CaMDR1, confer resistance to cyh (Sasnauskas et al, 1992) or to fluconazole, cyh, benomyl or sulphometuron methyl, respectively (Moran et al, 1998).…”
Section: Introductionmentioning
confidence: 99%